Effects of capillarity on pool boiling using nano-textured surfaces through electrosprayed BiVO4 nano-pillars. (2nd November 2017) - Jo, Hong Seok; Kim, Min-Woo; Kim, Karam; An, Seongpil; Kim, Yong Il; James, Scott C.; Choi, Jeehoon; Yoon, Sam S.
Highlights: Pool boiling enhancement through wettability control using nanotextured surfaces was demonstrated. Bismuth vanadate (BiVO4 ) was electrosprayed and nano-pillars are formed. The nano-pillars provided numerous bubble nucleation sites because of increased surface area. Both the critical heat flux and effective heat transfer coefficient increased with nano-pillar height. Abstract: Pool boiling is a mechanism by which heat is removed by changing the phase of a coolant from liquid to vapor. Surface wettability, which drives coolant capillarity, has a profound effect on the boiling process. We demonstrate pool boiling enhancement through wettability control using electrosprayed, nano-textured surfaces of bismuth vanadate (BiVO4 ). When a BiVO4 liquid precursor is electrostatically charged and sprayed, submicron droplets are formed and their acceleration is driven by the electrostatic force established between the nozzle exit and substrate. As droplets approach the substrate, Brownian diffusion takes place and an opposing thermophoretic force impedes the dynamic motion of evaporating droplets. As a result, nano-pillars are formed, whose physical sizes change the wettability of a surface and change pool-boiling phenomenon. The surface wettabilities of nano-textured surfaces were quantified with the water contact angle. Increased spraying time resulted in greater nano-pillar structure heights. Both the critical heat flux and effective heat transfer coefficient increased with nano-pillar height. However, excessively tall pillars had an adverse effect on pool-boiling through trapping of nucleated bubbles near the heat surface, which hindered efficient heat transfer.